Measuring e-service quality: a review of literature. (20th February 2020) - Shankar, Amit; Datta, Biplab
In the competitive electronic service (e-service) context, favourable consumer perception about performance is the key to success and marketers are keen to explore consumers' perceived service quality. Therefore, several scales have been developed to evaluate electronic service quality (e-SQ) in different contexts. This study explores methodological issues relating to the scale development process while undertaking content analysis of e-SQ literature. The study also focuses on the identification of crucial dimensions of e-SQ measurement scale in different e-service contexts. The review indicates that privacy and security, website design, responsiveness, efficiency, reliability, ease of use and system availability are prominent measures of e-SQ regardless of the context. This study also provides a comprehensive framework including antecedents and outcomes of e-SQ to help managers and researchers in evaluating e-SQ.